Sentiment Analysis and Comment Network of KompasTV YouTube Video on The First Vice-Presidential Debate In 2024 Presidential Election - Salsabilla, Syifa Ayu; Gema Nusantara Bakry; FX. Ari Agung Prastowo (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2024)
The 2024 Presidential Election (Pilpres) in Indonesia is a significant event involving vice-presidential candidate debates (Cawapres). This study aims to analyze sentiment and comment networks on KompasTV's YouTube debate video using a Social Network Analysis (SNA) approach. Data were collected from YouTube comments, analyzed using Netlytic and Gephi to identify public sentiment and key actors. Results show that interactions between actors are relatively easy, with positive comments dominating. The word "Gibran" appears most frequently, indicating attention on one candidate. The user fachrurrozinoorkhomarudin1253 has the highest degree centrality, while Lena_Palma has the highest betweenness centrality, indicating significant influence within the network. Conclusion: The Cawapres debate generates active interactions on YouTube, with public sentiment tending to be positive.